AN ANALYSIS OF THE USE OF CAPITAL LETTERS ON THE THESIS ABSTRACTS OF PGSD STUDENTS GRADUATE IN 2019 - Fitri Wahyuni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
One of the common problems in writing is spelling errors. This study aims to analyze the capital letters in the thesis abstract of PGSD students who graduate in 2019. Based on the results, the use of capital letters got lowest with a percentage of 33%, capital letters as the first letter of the direct passage, and capital as the first letter of every word (including perfect re-words) in the titles of books, essays, articles and papers and magazine and newspaper names, except for assignments such as in, to, from, which and and for not in the initial position. The use of capital letters got highest category with a percentage of 100%, capital letters as the first letter of the element of the person's name, including the nickname, capital letter as the first letter of the name of the position and rank followed by the person's name or used as a substitute name the name of a particular person, the name of the institution, or the name of the place, capital letters as the first letter of the name of the year, month, day, and holiday, capital letters as the first letter of the abbreviation for title greeting.